Comparative Reliability Assessment of Tooth Volume Measurement with Different Three-Dimensional Imaging Software. - Rasheed, Tara Ali; Shehab Al Hamdany, Afrah Khazal; Rauf, Aras Maruf (BioMed Research International, 2020)
Objective. To evaluate the in vivo tooth volume through VRMesh and 3Matic programs and to compare the measurements to the physical volume. So, the aim of the study was to ensure the reliability and sensitivity of the three-dimensional software (VRMesh and 3Matic) in measuring tooth volume. Material and Methods. The volume of 26 extracted upper first premolars from orthodontic patients who had CBCT before orthodontic treatment were measured. Two different commercial programs, which were VRMesh and 3Matic, were used to calculate the volume of the segmented upper first premolar from CBCT. The in vivo tooth volume was compared to the physical tooth volume to examine the accuracy of the two software in measuring the tooth volume. Results. The difference between the mean of the in vivo and in vitro tooth volume measurements was too small, making it clinically nonsignificant. ANOVA test was used as a statistical tool, and no statistically significant difference was noticed among the measurements. The values were normally distributed when tested for normality by Kolmogorov-Smirnov and Shapiro-Wilk test. P value less than or equal to 0.05 (P ≤ 0.05) was considered statistically significant. Conclusion. The assessment of the in vivo tooth volume measurement with different three-dimensional imaging software (VRMesh and 3Matic) programs in comparison with the tooth physical volume is reliable. The use of a mouse pen during the refining stage of the segmentation may have increased the accuracy of the procedure. The determined in vivo tooth volumes are dependable and can be applied in orthodontic diagnosis and treatment planning.